The Association between Antidepressant Medications and Coronary Heart Disease in Brazil: A Cross-Sectional Analysis on the Brazilian Longitudinal Study of Adult Health (ELSA-Brazil) - Kemp, Andrew H.; Brunoni, Andre R.; Bittencourt, Marcio S.; Nunes, Maria A.; Benseñor, Isabela M.; Lotufo, Paulo A. (Frontiers in Public Health, 2015)
Background: Recent studies have highlighted associations between use of antidepressant medications and coronary heart disease (CHD). Tricyclic antidepressants are not recommended in patients with CHD as they may increase morbidity and mortality. However, this class of antidepressants are freely prescribed in public health pharmacies, while access to other classes of antidepressants is restricted in Brazil. Here we examine the associations between antidepressant use and prevalent CHD in a large cohort from Brazil. Methods: Participants included 14,994 civil servants aged 35 to 74 from the baseline assessment of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). CHD (n=710) included stable angina, myocardial infarction and coronary revascularization. Univariate (unadjusted) and multivariate (adjusted) logistic regression analyses were conducted to estimate odds ratios and confidence intervals. Results: After full adjustment for covariates, tricyclic antidepressants (TCA) use (n=156) was associated with a 2-fold increase in prevalent CHD, relative to non-use (n=14,076). Additional sensitivity analysis revealed a three-fold association for myocardial infarction (OR: 2.962, 95% CI: 1.413-6.210) and coronary revascularization (OR: 2.915, 95% CI: 1.275-6.662). There were no significant associations between antidepressant use and stable angina pectoris. Conclusions: Findings highlight a strong association between TCA use and prevalent CHD. While the cross-sectional design is an important limitation of the present study, findings have important implications for the treatment of cardiac patients in Brazil.